PS 05-08 A COMPARATIVE STUDY OF ANEROID BLOOD PRESSURE MEASURING DEVICE AND DIGITAL BLOOD PRESSURE MONITOR VERSUS MERCURY SPHYGMOMANOMETER. (September 2016) - Gutch, Manish; Kumar, Sukriti; Reddy, Himanshu; Singh, Narendra
Abstract : Objective: To compare accuracy of aneroid and digital blood pressure instrument in comparison to mercury sphygmomanometer in supine as well as in standing position. To check postural changes in BP by aneroid and digital BP instrument in comparison to mercury sphygmomanometer. Design and method: This study has been enrolled patients visiting OPD and IPD patients department of medicine of KGMU Lucknow. Patients of age >12 years, of either gender were included in study. B.P of patient first measured with a mercury device using same arm. Blood Pressure in supine and standing position by mercury sphygmomanometer then aneroid and then digital Blood Pressure instrument. Results: Mean SBP in supine position are 127.44 + 12.25, 132.91 + 13.09 and 141.01 + 14.35 mmHg respectively and mean SBP finding in standing position are 122.75 + 12.34, 127.42 + 14.20 and 133.82 + 14.37 mmHg respectively by mercury, aneroid and digital manometer. Mean DBP in supine position are 80.49 + 8.80, 85.56 + 9.69 and 90.65 + 12.50 mmHg respectively and mean DBP in standing position are 78.79 + 8.82, 82.05 + 11.49 and 86.03 + 11.96 mmHg by mercury, aneroid and digital manometer respectively. The postural change in SBP (Supine Vs standing) are −8.43 + 4.27, −9.16 + 5.95 and −10.12 + 7.65 mmHg respectively and in DBP are −4.88 + 5.36, −6.39 + 6.54 and −6.98 + 8.98 mmHg by mercury, aneroid and digital manometer respectively. Conclusions: Compared to mercury, both aneroid and digital sphygmomanometers provided significantly higher mean values for both sitting and supine positions on overall evaluation (p < 0.001).